NEU3 activity enhances EGFR activation without affecting EGFR expression and acts on its sialylation levels. (28th April 2015) - Mozzi, Alessandra; Forcella, Matilde; Riva, Alice; Difrancesco, Carlotta; Molinari, Francesca; Martin, Vittoria; Papini, Nadia; Bernasconi, Barbara; Nonnis, Simona; Tedeschi, Gabriella; Mazzucchelli, Luca; Monti, Eugenio; et al.
Abstract : Several studies performed over the last decade have focused on the role of sialylation in the progression of cancer and, in particular, on the association between deregulation of sialidases and tumorigenic transformation. The plasma membrane-associated sialidase NEU3 is often deregulated in colorectal cancer (CRC), and it was shown that this enzyme co-immunoprecipitates in HeLa cells with epidermal growth factor receptor (EGFR), the molecular target of most recent monoclonal antibody-based therapies against CRC. To investigate the role of NEU3 sialidase on EGFR deregulation in CRC, we first collected data on NEU3 gene expression levels from a library of commercial colon cell lines, demonstrating that NEU3 transcription is upregulated in these cell lines. We also found EGFR to be hyperphosphorylated in all cell lines, with the exception of SW620 cells and the CCD841 normal intestinal cell line. By comparing the effects induced by overexpression of either the wild-type or the inactive mutant form of NEU3 on EGFR, we demonstrated that the active form of NEU3 enhanced receptor activation without affecting EGFR mRNA or protein expression. Moreover, through western blots and mass spectrometry analysis, we found that EGFR immunoprecipitated from cells overexpressing active NEU3, unlike the receptor from mock cells and cells overexpressing inactive NEU3, is desialylated. On the whole, our data demonstrate that, besides the already reported indirect EGFR activation through GM3, sialidase NEU3 could also play a role on EGFR activation through its desialylation.